Pelatihan dan Pendampingan Manajemen Perpustakaan Sekolah Berbasis Teknologi Informasi - Setiawan .; Moch Syahri; Dwi Novita Ernaningsih; Inawati; Amalia Nurma Dewi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Complex issues in school libraries are very diverse, from human resources, budget funds, book procurement, the technology system used is something that deserves attention, because the purpose of the school library is as a learning center, and information, as a learning resource center means that the school must try and clean up to present the latest collections, informative and according to the needs of the school. The school library has a very important role in the success of education. Therefore, school library facilities need attention. One of the facilities that help librarian activities is information technology-based library management. With library management, all library activities can run according to good library standards. Also, students can more easily and freely take advantage of the library collections in it. Information technology-based library management is activities that aim to assist library managers, the school, in creating libraries that comply with the standards set by the National Library. The activities carried out include (a) Providing information about how to manage library services, especially the Tsanawiyah library in Probolinggo Regency. (b) Providing knowledge on the procedures for managing the library at the Information Technology-based Tsanawiyah Library 2. (c) Instilling skills in Tsanawiyah library managers while studying. MTsN 2 Malang is under the auspices of the Ministry of Religion, course it must also have a good library, well managed, and course there is a role for the teaching staff in the library department to make the library the heart of information and the heart of education.